Finding Lost Childhoods : Supporting Care-Leavers to Access Personal Records - Murray, Suellen (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores care-leavers' access to their personal records. People who grew up in care in previous decades may know little about their family nor understand why they were placed in care nor how decisions were made about their lives. Personal records can be a source of this information. Murray posits that it is crucial that those releasing these records understand their significance. Taking a person-centred approach, the book is based on the moving life history accounts of people who have sought their records. Finding Lost Childhoods highlights the importance of records to their identity formation, recounts what they discovered about themselves and their family, and discusses the consequences of finding this information. With a focus on policy and practice implications, the book will be of particular interest to those engaged in the work of releasing records, as well as care-leavers themselves, professional bodies, and students and scholars with an interest in social work, policy studies, welfare studies and youth work.
Keywords: Social sciences.; Childhood.; Adolescence.; Social groups.; Families.; Families -- Social aspects.; Social policy.; Social service.; elektronické knihy; electronic books